Global Research on Menstrual Disorders and Adolescent Reproductive Health Outcomes (1980–2025): A Bibliometric and Science Mapping Analysis - Liliana, Anita; Melania Wahyuningsih; Herliana Riska; Khasanah, Nur (Rifa'Institute, 2026)
Menstrual health has emerged as a critical public health priority, yet comprehensive mapping of research evolution, geographic disparities, and thematic trajectories remains absent. This bibliometric analysis systematically characterizes the global research landscape on menstrual disorders and adolescent reproductive health outcomes. Following PRISMA guidelines, 544 Scopus-indexed articles published between 1980-2025 were analyzed using Biblioshiny (R Bibliometrix package version 4.1.3) and VOSviewer version 1.6.19. Extracted metrics included temporal productivity, citation patterns, authorship networks, institutional contributions, geographic distribution, international collaboration structures, and thematic evolution through keyword co-occurrence analysis. The Louvain modularity algorithm identified research domain clusters. While menstrual health research demonstrates quantitative expansion and rhetorical paradigm shifts toward biopsychosocial integration, substantial implementation gaps, geographic inequities, and thematic fragmentation persist. The field requires decisive pivot toward implementation science, digital innovation, decolonial knowledge production, and adolescent-centered translational research to achieve population health impact. School-based digital screening systems represent untapped opportunity for early identification and intervention.